Comparison of C-arm Computed Tomography and Digital Subtraction Angiography in Patients with Chronic Thromboembolic Pulmonary Hypertension - Hinrichs, Jan B.; Marquardt, Steffen; von Falck, Christian; Hoeper, Marius M.; Olsson, Karen M.; Wacker, Frank K.; Meyer, Bernhard C. (Cardiovascular and interventional radiology, 2016)
Purpose To assess the feasibility and diagnostic performance of contrast-enhanced, C-arm computed tomography (CACT) of the pulmonary arteries compared to digital subtraction angiography (DSA) in patients suffering from chronic thromboembolic pulmonary hypertension (CTEPH). Materials Fifty-two patients with CTEPH underwent ECG-gated DSA and contrast-enhanced CACT. Two readers (R1, R2) independently evaluated pulmonary artery segments and their sub-segmental branching using DSA and CACT for optimal image quality. Afterwards, the diagnostic findings, i.e., intraluminal filling defects, stenosis, and occlusion, were compared. Inter-modality and inter-observer agreement was calculated, and subsequently consensus reading was done and correlated to a reference standard representing the overall consensus of both modalities. Fisher’s exact test and Cohen’s Kappa were applied. Results A total of 1352 pulmonary segments were evaluated, of which 1255 (92.8 %) on DSA and 1256 (92.9 %) on CACT were rated to be fully diagnostic. The main causes of the non-diagnostic image quality were motion artifacts on CACT (R1:37, R2:78) and insufficient contrast enhancement on DSA (R1:59, R2:38). Inter-observer agreement was good for DSA ( κ = 0.74) and CACT ( κ = 0.75), while inter-modality agreement was moderate (R1: κ = 0.46, R2: κ = 0.47). Compared to the reference standard, the inter-modality agreement for CACT was excellent ( κ = 0.96), whereas it was inferior for DSA ( κ = 0.61) due to the higher number of abnormal consensus findings read as normal on DSA. Conclusion CACT of the pulmonary arteries is feasible and provides additional information to DSA. CACT has the potential to improve the diagnostic work-up of patients with CTEPH and may be particularly useful prior to surgical or interventional treatment.